Get to know ... Food service equipment & supplies - Maggio, Mary; Deyo, John; Learning Zone Express (Firm). (Owatonna, MN : Learning Zonexpress, 2009)
Students will learn the basics about equipment and tools used in foodservice kitchens.
Title from container.
Writers, Mary Maggio, David Christopherson, Timothy Kelly.
Presented by Dave Christopherson, Tim Cockram, Jason Hudock.
For audience grade 9 - Adult.
DVD format.
Keywords: Food service -- Equipment and supplies; Kitchen utensils; Food service equipment industry; Instructional videos